2021
DOI: 10.3390/jcm10204762
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients at Risk for Medication-Related Osteonecrosis of the Jaw. A Case and Control Study Analyzing Predictors of MRONJ Onset

Abstract: The goal of this investigation was to identify potential risk factors to predict the onset of medication-related osteonecrosis of the jaw (MRONJ). Through the identification of the multiple variables positively associated to MRONJ, we aim to write a paradigm for integrated MRONJ risk assessment built on the combined analysis of systemic and local risk factors. The characteristics of a cohort of cancer patients treated with zoledronic acid and/or denosumab were investigated; beyond the set of proven risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 86 publications
2
14
0
Order By: Relevance
“…There was study using multiple logistic regression model showed that breast, multiple myeloma, and prostate cancer involved a significantly higher risk compared to lung cancer. 34 However, Because of the limiting of literature information, it was not possible to analyze these subsets of cancers. Limones et al 35 reported that denosumab is related with higher risks of developing MRONJ than zoledronic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was study using multiple logistic regression model showed that breast, multiple myeloma, and prostate cancer involved a significantly higher risk compared to lung cancer. 34 However, Because of the limiting of literature information, it was not possible to analyze these subsets of cancers. Limones et al 35 reported that denosumab is related with higher risks of developing MRONJ than zoledronic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations. There was study using multiple logistic regression model showed that breast, multiple myeloma, and prostate cancer involved a significantly higher risk compared to lung cancer 34. However, Because of the limiting of literature information, it was not possible to analyze these subsets of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, antiresorptive agents are commonly prescribed in multiple myeloma. Cyclophosphamide has been reported to increase the risk of BRONJ among multiple myeloma patients receiving Palmidronate therapy [ 36 ], and a dose-dependent effect has been observed in animal experiments [ 19 ]. The combination of Cyclophosphamide with zoledronic acid has been shown to upregulate 1 L-6 and reduce the expression of CCR-7, CXCL12, CXCR4, and CD105 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medication related osteonecrosis of the jaws (MRONJ) in cancer patients has been associated with multiple predictors including chemotherapy, cancer type (breast, prostate cancer and multiple myeloma), bisphosphonate zolendronic acid, denosumab, and novel anticancer agents, reflecting a complex and cumulative risk structure [ 19 ]. Coadministration of anticancer drug cyclophosphamide with bisphosphonate zolendronic acid was found to induce BRONJ in a dose-dependent manner with increase in the dose of cyclophosphamide [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a slightly higher incidence of MRONJ has been reported for Dmab 4,5,8,11 . Currently, evidence from clinical practice 12–25 in oncological settings is based mainly on small patient samples 14–17 reporting on bone‐modifying agents in general, without clarifying Dmab and eventual risk factors role in the development of MRONJ 18–26 . Only few real‐world studies 13–17 focused on MRONJ related to Dmab administration.…”
Section: Introductionmentioning
confidence: 99%